Evaluation of Cybersecurity Implementation in the Master Plan for Information Technology (RITI) of Indonesian Banking in the Digital Era - Erlangga, Faezal; Abdurrahman, Lukman (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
The purpose of this study is to evaluate the implementation of cybersecurity policies outlined in the Master Plan for Information Technology (RITI) within Indonesia’s digital banking sector, with a specific focus on assessing their effectiveness in mitigating increasingly sophisticated cyber threats. Employing a descriptive qualitative research design, this study uses a literature review approach based on credible sources, including peer-reviewed scientific articles, regulatory policy documents, and case studies involving cyberattacks on Indonesian banks. The findings indicate that while the regulatory frameworks established by Otoritas Jasa Keuangan (OJK) and Bank Indonesia (BI) serve as a solid foundation for cybersecurity governance, their implementation remains inconsistent across institutions, particularly due to resource disparities between large and small banks. Smaller banks often face significant obstacles such as limited IT infrastructure, insufficient human resources, and lack of technical oversight, which hinder the full adoption of cybersecurity standards. The discussion highlights the need for more proactive supervision, tailored technical support, and the adoption of AI-driven solutions for real-time threat detection and rapid incident response. The study concludes that fostering stronger collaboration between regulatory bodies, financial institutions, and private technology providers is crucial for creating an integrated and resilient cybersecurity ecosystem. These efforts are essential not only for strengthening system resilience but also for increasing customer trust in digital banking services.